U/Pb Detrital Zircon Provenance of Mid-Pennsylvanian Sediments into the Anadarko Basin: Implications for Paleogeography and Sequence Stratigraphy - de Jesus, Dalila Armanda (My University, 2021)
Late Paleozoic tectonism coupled with high-frequency climatic variations influenced sediment dispersal patterns across the midcontinent that resulted in frequent shifts of sediment sources to depocenters. Despite the numerous provenance studies conducted in Pennsylvanian strata of the midcontinent, fundamental questions remain unresolved regarding sediment transport into the Anadarko Basin and its spatio-temporal variation. The prolific Middle Pennsylvanian Red Fork Sandstone (Cherokee Group) of the Anadarko Basin, Oklahoma, provides an exceptional opportunity to address this issue. The Red Fork Sandstone is interpreted as a series of ribbon and sheet sandstones deposited in fluvial, deltaic, shelfal and deep-water environments during a time of rapid tectonic subsidence and substantial (in magnitude and frequency) glacioeustatic fluctuations. This study tests whether Middle Pennsylvanian sediment-routing systems into the Anadarko Basin varied spatially and on sequence-stratigraphic scales. Well-log correlation of three incised valley systems along the eastern margin of the Anadarko Basin was coupled with core analysis of three cores that represent each of the incised valley fills. Modal mineralogy of seven samples and 2011 concordant detrital zircon U-Pb ages from seven Red Fork Sandstone samples were collected from these three cores. Facies and facies-stacking interpretations were combined with sandstone compositions buttressed with the U/Pb detrital-zircon geochronology to assess the mineralogy, sequence stratigraphy, and provenance signatures of the units. The facies within the cored intervals of the Red Fork Sandstone are inferred to represent tidal, marginal marine, marine and non-marine nvironments primarily and exhibit stacking patterns that suggest each of the cored intervals contain a major sequence boundary overlain by a lowstand systems tract. Two of the cored intervals (Cores 2 and 3) contain stacked facies that represent transgressive and highstand system tracts, but differences in the facies expression of these tracts between the two cores suggest differences in environments and response to the relative sea level rise; the third core is incomplete (Core 1) and does not contain evidence of the transgressive or highstand systems tracts. Differences in U-Pb ages of the detrital zircons indicate that sand provenance varied among the three cored intervals. Three major detrital zircon signatures characterize the sandstones in this study: Type 1, 2 and 3. Type 1, which corresponds to sandstones of sublith-litharenite composition, occurs within the lowstand system tracts of the northern and north-central Anadarko Shelf (Cores 1 and 2) and displays a prominent age cluster corresponding to the Neoproterozoic Northern Appalachian (560-740 Ma) basement terrane. Type 2, which corresponds to sandstones of quartzarenite compositions, occurs within the lowstand and highstand system tracts of the eastern Anadarko Shelf (Core 3) and is characterized by a high percentage of Grenvillian-age (900-1300 Ma) grains. Finally, Type 3, which is only found in the highstand system tract sands of Core 2, contains a more mixed source reflecting derivation from Grenvillian (900-1300 Ma) terranes and subordinate Yavapai-Mazatzal (1600-1800 Ma) and Granite Rhyolite (1300-1600 Ma) terranes. Comparative assessment of published U-Pb detrital zircon ages from time equivalent sandstones and exposed basement rocks across the North American craton indicates that Type 1, lowstand sandstones (also considering their metamorphic lithics content) from the northern and north-central shelf reflect sourcing by a distal, transcontinental dispersal system that originated in the Northern Appalachians, either by exhumation of peri-Gondwanan basement rocks or by recycling of Neoproterozoic sedimentary cover. These sandstones are interpreted to reflect a southwestward transport of sediments across the midcontinent and into the Anadarko Shelf and Basin during a time of sea level drawdown. Detrital zircon signatures from Type 2, low- and highstand, sandstones suggest both a major sourcing by a distal, extrabasinal fluvial system originating in the Central Appalachians, with a minor local midcontinent source, that likely had a sufficient sediment supply as to outpace relative sea level rise at least during initial rise. Type 3, highstand, sandstone zircon signatures suggest that within the area of the incised valleys along the northern shelf, the Neoproterozoic-rich sediment was not supplied, but likely trapped in fluvio-deltaic systems farther east as relative rise outpaced sediment supply and that the deposited sands were a mixture of reworking of the local sands and from the still active fluvio-deltaic system along the eastern Anadarko Shelf.
Keywords: Anadarko Basin; Provenance; Pennsylvanian; Zircon geochronology